Pancreatic tuberculosis: A close mimicker of malignancy - Soni, Ankita; Tyagi, Ruchita; Selhi, Pavneet Kaur; Sood, Ajit; Sood, Neena (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Soni A, Tyagi R, Selhi PK, Sood A, Sood N. Pancreatic tuberculosis: A close mimicker of malignancy. Turk J Gastroenterol 2019; 30(11): 1001-3.